A retrospective comparison of albumin versus mannitol priming fluid with relation to postoperative atrial fibrillation. Issue 11 (18th September 2022) - Binder, M. Scott; Wu, YingXing; Baker, Joseph W.; Rowe, Joseph F.; Wyatt, David A.; Choate, Cynthia; Poelzing, Steven; Joseph, Mark
Abstract: Background and Aim of the Study: Postoperative atrial fibrillation (POAF) is a common complication following cardiac surgery which can result in increased mortality and increased healthcare costs. During Hurricane Maria (2017), a nationwide shortage of mannitol occurred, and our institution switched to the utilization of albumin as a priming fluid solution. We observed decreased rates of POAF during that time and began alternating albumin and mannitol priming fluid solutions. We hypothesized this observation may be from altered perinexal conduction from albumin utilization. Methods: A retrospective chart review of all patients from January 2020 through December 2020 who underwent cardiac surgery was performed, to determine if albumin was associated with reduced POAF rates. Two hundred and thirteen patients were identified and 4 were excluded. Two hundred and nine patients (110 albumin priming fluid and 99 mannitol priming fluid) were included in our final analysis. Results: Analysis was performed for all patients with POAF and in patients with new‐onset AF (without a history of prior AF) after surgery. POAF rates showed no statistically significant difference between cohorts. For all patients, POAF occurred in 43% of the albumin subgroup and 47% of the mannitol subgroup ( p = .53) and for patients with new‐onset AF, POAF occurred in 35% of the albumin subgroup versus 42% of the mannitol subgroup ( p = .36). Logistic regression revealed that age, ejection fraction and cardiopulmonary bypass time was associated with POAF, in our cohort. Conclusions: The use of albumin compared to mannitol as priming fluid solutions was not associated with statistically significant reductions in POAF rate, in our population.